MOLECULAR IDENTIFICATION OF EGG PARASITOID, TELENOMUS SPP. (HYMENOPTERA: SCELIONIDAE) FROM SEVERAL LOCATIONS IN JAVA USING RAPD-PCR - NETTI YULIARTI; PURNAMA HIDAYAT; DAMAYANTI BUCHORI (SEAMEO BIOTROP, 2002)
Random amplified polymorphic DNA (RAPD) amplified by the polymerase chain reaction (PCR) was used to determine the differences of four Telenomus species and five populations of T. rowani from several locations in Java. Amplification of genomic DNA by using primer P2 (Amersham Pharmacia Biotech) indicated that each Telenomus species had a unique set of RAPD bands. Two bands which characterized the genus are estimated to be 300 and 430 bp. Each species had three specific bright bands except T. dignoides which only had two specific bright bands. However, no bands are unique to any of the five populations of T. rowani and all of the bands are less than 500 base-pair. Cluster analysis using UPGMA (Unweighed Pair Group Method With Arithmatic Mean) showed that the four Telenomus species consist of two groups, T. rowani and T. remusÂ in one cluster and T. dignus with T. dignoides belonging to another cluster. Key words : PCR-RAPD / clustering / Telenomus spp.